Influence of Hydrodynamic Disintegration on the Release of Organic and Nutrient Compounds From Activated Sludge. Issue 11 (2nd November 2017) - Walczak, Justyna; Zubrowska‐Sudol, Monika; Piechna, Paula
Abstract : The aim of the research is to assess the release of organic compounds and nutrients to liquid phase as a result of hydrodynamic disintegration (HD) of sludge. Six batch disintegration tests are conducted. The scope is a complex analysis of the release of organic compounds (soluble chemical oxygen demand [SCOD], volatile fatty acids [VFA]) and nutrients (soluble total nitrogen [STN], NO2 − ‐N, NO3 − ‐N, NH4 + ‐N, soluble total phosphorus [STP], PO4 3– ‐P) depending on the energy density (ϵL ) used during the HD process (70–350 kJ L −1 ). It is shown that an increase in ϵL is correlated with an increase in the disintegration degree (DD). This results in an increase in both the SCOD (including VFA) and in the soluble nutrient concentration (STN and STP). The value of ϵL, at which HD is conducted, also has an influence on the percentage share of VFA in soluble organic compounds released from activated sludge flocs and on the relationship between the SCOD/STN and SCOD/STP ratio. It is also shown that ϵL and the total solids concentration of disintegrated sludge have an influence on the costs of organic compounds acquired by the HD method. Low costs are obtained for ϵL  = 350 kJ L −1 (0.7–2.2 € kg −1 SCOD and 12.8–23.64.0 € kg −1 VFA), and for relatively high total solids (TS) concentrations (TS > 4%) (1.5–1.9 € kg −1 SCOD for ϵL  = 70 kJ kg −1 and 0.7–0.8 € kg −1 SCOD for ϵL  = 350 kJ L −1 ). Abstract : The aim of the study is to assess the release of organic compounds and nutrients to a liquid phase as a result of hydrodynamic disintegration of activated sludge. An increase in the amount of energy used in the hydrodynamic disintegration process is correlated with an increase in disintegration degree, organic compounds (including volatile fatty acids), and nutrients (nitrogen and phosphorus).